Development of screening method for intranasal influenza vaccine and adjuvant safety in preclinical study - Hiradate, Yuki; Sasaki, Eita; Momose, Haruka; Asanuma, Hideki; Furuhata, Keiko; Takai, Mamiko; Aoshi, Taiki; Yamada, Hiroshi; Ishii, Ken J.; Tanemura, Kentaro; Mizukami, Takuo; Hamaguchi, Isao (Biologicals, 2018)
Recently, many vaccine adjuvants have been developed; however, most of the newly developed adjuvants have been dropped out of preclinical and clinical trials owing to their unexpected toxicity. Thus, the development of highly quantitative and comparable screening methods for evaluating adjuvant safety is needed. In a previous study, we identified specific biomarkers for evaluating the safety of an intranasal influenza vaccine with CpG K3 adjuvant by comparing biomarker expression. We hypothesized that these biomarkers might be useful for screening newly developed adjuvant safety. We compared the expression of biomarkers in mouse lungs by the intranasal administration of 4 types of adjuvants: Alum, Pam3CSK4, NanoSiO2, and DMXAA with subvirion influenza vaccine. The control adjuvant alum did not show any significant increase in biomarker expression or preclinical parameters; however, NanoSiO2 and Pam3CSK4 increased the expression of biomarkers, such as Timp1 and Csf1. DMXAA at 300 μg induced the expression of over 80% of biomarkers. Hierarchical clustering analysis showed that 300 μg DMXAA was classified in the toxicity reference whole-particle influenza vaccine cluster. FACS analysis to confirm specific phenotypes that the number of T cells decreased in DMXAA-treated mouse lungs. Thus, our biomarkers are useful for initial adjuvant safety and toxicity screening. •We compared the safety biomarkers expression in mouse lungs by the intranasal administration of 4 types of adjuvants.•The aluminum as a safety adjuvant control did not show any significant increase in biomarker expression.•However, nanoSiO2 and Pam3CSK4 increased the expression of biomarkers, such as Timp1 and Csf1.•Hierarchical clustering suggested that DMXAA was similar to that of toxicity reference and found the leukopenic toxicity.•Our biomarkers are useful for initial adjuvant safety and toxicity screening.